Vitamin D Treatment for the Prevention of Falls in Older Adults: Systematic Review and Meta-Analysis - Kalyani, Rita Rastogi; Stein, Brady; Valiyil, Ritu; Manno, Rebecca; Maynard, Janet W.; Crews, Deidra C. (Journal of the American Geriatrics Society (JAGS), 2010)
OBJECTIVES: To systematically review and quantitatively synthesize the effect of vitamin D therapy on fall prevention in older adults. DESIGN: Systematic review and meta‐analysis. SETTING: MEDLINE, CINAHL, Web of Science, EMBASE, Cochrane Library, LILACS, bibliographies of selected articles, and previous systematic reviews through February 2009 were searched for eligible studies. PARTICIPANTS: Older adults (aged ≥60) who participated in randomized controlled trials that both investigated the effectiveness of vitamin D therapy in the prevention of falls and used an explicit fall definition. MEASUREMENTS: Two authors independently extracted data, including study characteristics, quality assessment, and outcomes. The I2 statistic was used to assess heterogeneity in a random‐effects model. RESULTS: Of 1,679 potentially relevant articles, 10 met inclusion criteria. In pooled analysis, vitamin D therapy (200–1,000 IU) resulted in 14% (relative risk (RR)=0.86, 95% confidence interval (CI)=0.79–0.93; I2=7%) fewer falls than calcium or placebo (number needed to treat =15). The following subgroups had significantly fewer falls: community‐dwelling (aged <80), adjunctive calcium supplementation, no history of fractures or falls, duration longer than 6 months, cholecalciferol, and dose of 800 IU or greater. Meta‐regression demonstrated no linear association between vitamin D dose or duration and treatment effect. Post hoc analysis including seven additional studies (17 total) without explicit fall definitions yielded smaller benefit (RR=0.92, 95% CI=0.87–0.98) and more heterogeneity (I2=36%) but found significant intergroup differences favoring adjunctive calcium over none (P=.001). CONCLUSION: Vitamin D treatment effectively reduces the risk of falls in older adults. Future studies should investigate whether particular populations or treatment regimens may have greater benefit.